ASEAN branding: Exploring the language styles of tourism slogans - Munder, Dania B. (JOALL (Journal of Applied Linguistics and Literature), 2024)
Creating the Association of Southeast Asian Nations (ASEAN), with its motto, one vision, one identity, and one community, holds an integral role in unifying Southeast Asian countries. With this, there is a need to achieve a united branding. Lerman, Morais, and Luna (2018) elaborate on the importance of being aware of the relationship between language and culture, which aids in creating a brand language that mirrors the culture of their target customers. With this study, brand advertisers can learn the importance of language branding and the differences in the language used to achieve a united ASEAN branding. In understanding ASEAN’s branding, Grey’s Language Style Theory was employed in the different pre-pandemic and post-pandemic tourism slogans, focusing on the syntactic and lexical features using the descriptive method. The study’s findings demonstrate that most syntactic forms of post-pandemic slogans have changed from phrases to sentences. It also reveals that most of the post-pandemic slogans used short sentences and simple, colloquial, and imperative language in their syntactic features. Most of the post-pandemic tourism slogans were modified for the lexical features to use simple vocabulary, glamorization, and repetition. Furthermore, the post-pandemic slogans suggest a more enthusiastic ASEAN tourism branding centered on passion, wonder, and love.